Gambaran Kadar Enzim AST ALT dan Bilirubin pada Pasien Sirosis Hepatis Akibat Infeksi VHB di RSUD. Dr. H. Moch. Ansari Saleh Banjarmasin - Hajrah Hidriya; Pebby Yolanda Erika Sucipto; Risnawati Risnawati; Ahmad Ripani (Politeknik Unggulan Kalimantan, 2025)
Hepatitis B constitutes a transmissible ailment that principally affects the liver, inducing acute and enduring conditions, specifically liver cirrhosis. This chronic hepatic disorder instigates a widespread mechanism involving nodule development and fibrosis within the liver structure. One of the markers of liver damage is an increase in aminotransferase enzyme levels and bilirubin levels. The aim of this inquiry was to quantify the percentage of AST, ALT enzyme levels and Bilirubin levels regarding patients with Hepatitis B Virus Infection at Dr. H. Moch. Ansari Saleh Hospital, Banjarmasin. The analytical framework employed a cross-sectional method utilizing medical records and datasets from the Clinical Pathology Laboratory at Dr. H. Moch. Ansari Saleh Hospital, Banjarmasin. Observations demonstrated a substantial rise in AST, ALT, and Bilirubin. The highest age group for AST, ALT, and bilirubin examination was 41-60 years old with 26 patients (60%) and the lowest age group was 61-70 years old with 6 patients (14%). Within the group of patients exhibiting liver cirrhosis attributed to Hepatitis B virus infection, AST, ALT, and bilirubin levels escalated significantly among males (67%) and females (33%). Derived from the study outcomes, it is concluded that the rise in AST, ALT, and bilirubin enzyme levels showed a marked increase in the 41-50 year age range, namely 26 patients (60%) and 43 patients (67%) of male gender.